2016
DOI: 10.1111/pde.12872
|View full text |Cite
|
Sign up to set email alerts
|

Crisaborole Topical Ointment, 2% in Patients Ages 2 to 17 Years with Atopic Dermatitis: A Phase 1b, Open‐Label, Maximal‐Use Systemic Exposure Study

Abstract: BackgroundPhosphodiesterase‐4 (PDE4) is a promising target in atopic dermatitis (AD) treatment. The pharmacokinetics (PK), safety, and efficacy of crisaborole topical ointment, 2% (formerly AN2728) (Anacor Pharmaceuticals, Palo Alto, CA), a boron‐based benzoxaborole PDE4 inhibitor, were evaluated in children with mild to moderate AD.MethodsThis phase 1b, open‐label, maximal‐use study of crisaborole topical ointment, 2% applied twice daily (dose 3 mg/cm2) for 28 days enrolled patients ages 2 to 17 years with ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(62 citation statements)
references
References 12 publications
2
59
0
1
Order By: Relevance
“…In the phase IIa adult study, 68 % experienced a decrease in ADSI in the crisaborole-treated lesion compared with only 20 % in the vehicle-treated lesion [137]. The phase IIa open-label adolescent study demonstrated that [70 % of subjects achieved an Investigator's Static Global Assessment (ISGA) score of 0 or 1 (clear or almost clear) with crisaborole [138,139]. Two post hoc pooled analyses of the four studies found that [80 % of subjects experienced a categorical shift of pruritus intensity (0-1.5 = no-mild, 2-3 = moderate-severe) at the earliest post-baseline efficacy assessment (day 8 or 15, depending on the study), and this effect was maintained for the duration of the study [140].…”
Section: Crisaborolementioning
confidence: 99%
See 1 more Smart Citation
“…In the phase IIa adult study, 68 % experienced a decrease in ADSI in the crisaborole-treated lesion compared with only 20 % in the vehicle-treated lesion [137]. The phase IIa open-label adolescent study demonstrated that [70 % of subjects achieved an Investigator's Static Global Assessment (ISGA) score of 0 or 1 (clear or almost clear) with crisaborole [138,139]. Two post hoc pooled analyses of the four studies found that [80 % of subjects experienced a categorical shift of pruritus intensity (0-1.5 = no-mild, 2-3 = moderate-severe) at the earliest post-baseline efficacy assessment (day 8 or 15, depending on the study), and this effect was maintained for the duration of the study [140].…”
Section: Crisaborolementioning
confidence: 99%
“…Crisaborole (AN-2728) is a boron-containing topical PDE4 inhibitor, for which three phase II trials in adolescents and adults have been published [136][137][138][139]. Results from the largest of these, a dose-justification study that enrolled adolescents, observed that bid application of crisaborole 2 % ointment resulted in total or partial clearance of target lesions in 62 % of subjects after 29 days of treatment and a 71 % reduction in the Atopic Dermatitis Severity Index (ADSI) score [136].…”
Section: Crisaborolementioning
confidence: 99%
“…Skin irritation scoring was based on the Draize scale [27]. Safety margins for crisaborole administered topically to mice were calculated based on area under the concentration-time curve (AUC 24 ), taking into account the systemic exposure of topically administered crisaborole in pediatric and adult patients with AD (plasma levels in a clinical study conducted by Anacor Pharmaceuticals, Inc; Maximal Use Systemic Exposure [MUSE]) [28].…”
Section: Toxicity Assessmentmentioning
confidence: 99%
“…Seven studies have been conducted on the topical formulation of the compound to date, and two of them have reached phase III (NCT02118792 and NCT02118766). Data on the previous phase I and II studies showed positive results across a accumulated cohort of 189 subjects with AD as young as 2 years of age [54,[56][57][58][59]. The first study conducted assessed the safety profile and pharmacokinetics in both children and adolescents under conditions with a supposed maximal use of topical crisaborole [56].…”
Section: Crisaborolementioning
confidence: 99%